2006
DOI: 10.1182/blood.v108.11.557.557
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing the Combination Therapy of Deferiprone (DFP) and Desferrioxamine (DFO) Versus DFP or DFO Monotherapy in Patients with Thalassemia Major.

Abstract: Several clinical studies have shown that the combination of deferiprone (DFP) with desferrioxamine (DFO) is efficacious with regard to decrease in serum ferritin (SF), reduction of liver iron concentration (LIC) and increase in urinary iron excretion (UIE) in patients (pts) suffering from thalassemia major (TM). However, there is lack of randomized controlled trials comparing the efficiacy and safety of the combination therapy versus DFP or DFO monotherapy. This is the first randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Proteinuria should be considered, if urine protein/creatinine ratio is ≥0.6 because urinary protein excretion is greater in beta thalassemia major compared to normal patients. 3 Aldudak et al has determined this limit as 0.7. 10 In a study conducted in our country, proteinuria due to deferasirox was observed in 7 of 37 patients (19%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Proteinuria should be considered, if urine protein/creatinine ratio is ≥0.6 because urinary protein excretion is greater in beta thalassemia major compared to normal patients. 3 Aldudak et al has determined this limit as 0.7. 10 In a study conducted in our country, proteinuria due to deferasirox was observed in 7 of 37 patients (19%).…”
Section: Discussionmentioning
confidence: 94%
“…Optimal treatment is used for patients according to treatment compliance and drug adverse effects. 3 Deferasirox is an iron chelator used in the treatment of B-thalassemia. One of the common side effects is nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Ten were multicentre trials (Calvaruso 2015; Elalfy 2015; Galanello 2006; Maggio 2009; Olivieri 1997; Pennell 2006; Pennell 2014; Taher 2017; Tanner 2007; Vichinsky 2007) and ranged from two centres in one country (Calvaruso 2015; Elalfy 2015; Olivieri 1997) to 44 centres in multiple countries (Vichinsky 2007). Six were single-centre trials (Aydinok 2007; Bahnasawy 2017; Badawy 2010; El Beshlawy 2008; Hassan 2016, Mourad 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants enrolled in the trials ranged from 24 (Aydinok 2007) to 213 (Maggio 2009). Sample-size calculations were reported in eight trials (Calvaruso 2015; Elalfy 2015; El Beshlawy 2008; Maggio 2009; Pennell 2006; Pennell 2014; Tanner 2007; Vichinsky 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation